AN ANALYSIS OF CHARACTERIZATION IN FAST AND FURIOUS PRESENT: HOBBS & SHAW - Ahmada, Raditya Wahyu Ramadhani; Saptanto, Deswandito Dwi (Universitas Ngudi Waluyo, 2023)
Character is an important element in fictional work besides the other elements. In fiction, character reveals a textual representation of human being, or occasionally another creature. Character is the player in the story and it makes the story alive. Every character in a story has characterization. Characterization is the process of conveying information about characters in fiction. In other words, characterization is the way an author describes their characters’ characteristic in the story. The writer chose “An Analysis of Characterization in Fast and Furious Present: Hobbs & Shaw” as the title of his research. This research has two purposes: to find out How are instrinsic aspects generally described in Fast & Furious Present: Hobbs & Shaw, and to find How the protagonist and antagonist characterizations are described in Fast & Furious Present: Hobbs & Shaw. The writer limits the research into analyzing only five main characters that found in the story that the writer found after watching throughout the movie.